2023
DOI: 10.1002/bmc.5595
|View full text |Cite
|
Sign up to set email alerts
|

Combining lipidomics and efficacy‐oriented compatibility revealed that Qi Ge decoction compatibility improved lipid metabolism in hyperlipidemic rats

Abstract: The mechanism underlying traditional Chinese medicine (TCM) compatibility is difficult to understand. This study combined lipidomics and efficacy-oriented compatibility to explore underlying compatibility mechanisms of Qi Ge decoction (QG) for improving lipid metabolism in hyperlipidemic rats. The QG was divided into three groups according to the efficacy group strategy: the Huangqi-Gegen (HG), Chenpi (CP), and QG groups. Hyperlipidemic rats were treated with QG, HG, CP, or atorvastatin for 3 weeks. The mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Preliminary research has established a QG fingerprint (Ke et al, 2017), determined the optimal ratio and extraction process (Huang et al, 2017;Li, 2016), identified its main components (Li et al, 2022;Yu et al, 2021), and confirmed its pharmacological efficacy (Zhou, 2021;Zhou et al, 2021;Zhu, 2019). QG has lipid-lowering and hepatoprotective effects in hyperlipidemic rats (Fan et al, 2022(Fan et al, , 2023Peng et al, 2019Peng et al, , 2023, but its effective substances and their targets of action remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary research has established a QG fingerprint (Ke et al, 2017), determined the optimal ratio and extraction process (Huang et al, 2017;Li, 2016), identified its main components (Li et al, 2022;Yu et al, 2021), and confirmed its pharmacological efficacy (Zhou, 2021;Zhou et al, 2021;Zhu, 2019). QG has lipid-lowering and hepatoprotective effects in hyperlipidemic rats (Fan et al, 2022(Fan et al, , 2023Peng et al, 2019Peng et al, , 2023, but its effective substances and their targets of action remain unclear.…”
Section: Introductionmentioning
confidence: 99%